Makna Budaya Bajapuik dalam Pernikahan Etnis Minangkabau di Kota Pariaman Sumatra Barat - Anita, Nurul; Brata, Nugroho Trisnu (Department of Anthropology, 2023)
Bajapuik is a wedding tradition characteristic of the Pariaman area, West Sumatra. Bajapuik culture considers the obligation of women to give some money to men. The amount of japuik money women must prepare depends on the agreement between the parties. The purpose of this study was to analyze the meaning of bajapuik culture in community marriages in the city of Pariaman. The data collection technique in this study employs observation, interviews and documentation studies. In contrast, data analysis uses data reduction, presentation, and conclusion. The validity of the data uses triangulation. Bajapuik culture has undergone many changes, one of which is in the value of japuik money. Historically, moral values were prioritized when indigenous people implemented the bajapuik culture. Still, nowadays, economic values are prioritized due to the strengthening of modern culture and materialism culture. The meaning of the Bajapuik culture in the Pariaman area is as a form of appreciation for men. The japuik money given by the woman to the man, money can later use to finance the household with his wife. This study suggests that people outside the Pariaman area better understand the meaning of the bajapuik culture itself and do not assume that men in Pariaman city are